2019 14th Annual Conference System of Systems Engineering (SoSE) 2019
DOI: 10.1109/sysose.2019.8753863
|View full text |Cite
|
Sign up to set email alerts
|

Architectural reasoning in the conceptual phase - a case study in the oil and gas industry

Abstract: This paper evaluates the use of architectural reasoning to explore the problem space in a system development project in the oil and gas industry. The suppliers in this industry have traditionally been tailor-making their systems for each delivery project. To improve the systems offering across the client and project portfolio, the suppliers must put more effort in the conceptual phase to explore the design space. Architectural reasoning is the process of transferring problem and solution know-how into a new sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Other industries have im-plemented Integrated Product and Process teams to ensure involvement from all stakeholders. The company is currently testing out such operational model in one of their development projects and have seen clear benefits from having multidisciplinary teams, (Engen, Falk, and Muller 2019). We also recommend allocating a resource from Life-of-Field to every Quality Notification report, to give Life-of-Field the responsibility and mandate to follow up on product improvement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other industries have im-plemented Integrated Product and Process teams to ensure involvement from all stakeholders. The company is currently testing out such operational model in one of their development projects and have seen clear benefits from having multidisciplinary teams, (Engen, Falk, and Muller 2019). We also recommend allocating a resource from Life-of-Field to every Quality Notification report, to give Life-of-Field the responsibility and mandate to follow up on product improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the needs is vital for overall project success (Callister & Andersson 2016). However, the oil and gas industry are immature in implementation of system engineering and design knowledge is not properly documented (Falk, Ulsvik, Engen & Syverud, 2019), increasing the risk of poor design choices and subsequent cost overruns and schedule delays.…”
Section: Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A case study recently conducted in the subsea domain, (Engen, et al, 2019), evaluates architectural reasoning when applied in the conceptual phase of a development project. The authors identified sharing architectural knowledge as a main challenge in the early phase of a subsea project and propose A3AO, in combination with conceptual modeling, as a topic for further investigation (Engen, et al, 2019). This proposal is supported by other case studies in the subsea domain (Muller, et al, 2015) (Boge & Falk, 2019).…”
Section: Manifoldmentioning
confidence: 99%
“…The requirement engineering in the oil and gas industry has historically been text based and managed in several word documents and Excel sheets. The requirement specifications provided by the client oil company are typically extensive and detailed, giving a mix of requirements and detailed requirements (Damien Wee & Muller, 2016;Engen, Falk, & Muller, 2019). The use of text-based prose in the industry and company standards makes it difficult for end users to fully understand and verify the requirements (Zager, McKinney, Reed, 2019).…”
Section: Introductionmentioning
confidence: 99%